A new syndrome, congenital extraocular muscle fibrosis with ulnar hand anomalies, maps to chromosome 21qter. Issue 5 (29th April 2005) - Tukel, T; Uzumcu, A; Gezer, A; Kayserili, H; Yuksel-Apak, M; Uyguner, O; Gultekin, S H; Hennies, H-C; Nurnberg, P; Desnick, R J; Wollnik, B
Abstract : Background: Congenital fibrosis of the extraocular muscles (CFEOM) is a heterogeneous group of disorders that may be associated with other anomalies. The association of a CFEOM syndrome with ulnar hand abnormalities (CFEOM/U) has not been reported to date. Objective: To describe a new autosomal recessive syndrome of CFEOM and ulnar hand abnormalities, and localise the disease causing gene. Methods: Clinical evaluation of the affected members and positional mapping. Results: Six affected patients with CFEOM/U (aged 2 to 29 years) from a large consanguineous Turkish family were studied. Ophthalmological involvement was characterised by non-progressive restrictive ophthalmoplegia with blepharoptosis of the right eye. The postaxial oligodactyly/oligosyndactyly of the hands was more severe on the right side. A genome-wide scan established linkage of this new autosomal recessive syndrome to a locus on chromosome 21qter. The multipoint LOD score was 4.53 at microsatellite marker D21S1259, and fine mapping defined a ∼1.5 Mb critical region between microsatellite marker D21S1897 and the telomere of the long arm. Conclusions: CFEOM/U maps to a 1.5 Mb region at chromosome 21qter. Future identification of the disease causing gene may provide insights into the development of the extraocular muscles and brain stem α motor neurones, as well as anteroposterior limb development.